PERAN PERGURUAN TINGGI ISLAM DI INDONESIA DALAM DISEMINASI NILAI-NILAI MODERASI BERAGAMA UNTUK MASYARAKAT GLOBAL - Djunawir Syafar; Firman Sidik (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the role of Islamic universities in Indonesia in addressing global issues. This study describes the implementation of the Religious Moderation program at three Islamic universities, namely UIN Sunan Kalijaga Yogyakarta, UIN Syarif Hidayatullah Jakarta, and Universitas Islam Internasional Indonesia (UIII). The three universities have special programs related to Religious Moderation in responding to global socio-religious issues. This study employs a qualitative approach, namely literature review, sources from university and government websites. The results of this study indicate that: First, Islamic universities play an important role in disseminating the values of Religious Moderation because they are supported by constitutional, contextual, and institutional factors. Second, the strategies implemented by Islamic universities include integrating the values of Religious Moderation into the learning process, research, community service, institutionalization of Religious Moderation, international scholarship programs, and international cooperation. Third, the challenges faced by Islamic universities, namely ideological, political, social, and economic contestation, locally, nationally, and globally. The results of this study can serve as a reference for government agencies and educational institutions in formulating policies and work programs related to the implementation of Religious Moderation in responding to global socio-religious challenges.